Prevalence of symptoms in patients poisoned with iron in Ahvaz Razi Hospital in 2014-2017 - Ali hassan Rahmani; Shahrzad Molavinia; Fatemeh Boustani (Asia Pacific Journal of Medical Toxicology, 2020)
Background: Iron is an important element for normal cell metabolism, but in excess amounts is quite cytotoxic, and even deadly. Iron poisoning is a calamity repeated many times in the world. The clinical signs of the patients include gastrointestinal symptoms, a short period of relative stability, Cardiogenic shock, liver failure, and scarring of the gastrointestinal tract. Iron tablets are specifically tempting to children because they are similar to candy. Iron overdose in adults is usually to attempt suicide. Methods: The present study is a descriptive-analytic study based on hospital information, that was conducted among the patients affected with iron poisoning admitted to Razi hospital (a referral medical setting for poisoning treatment in southwest Iran) during 2014-2017. Patient information has been extracted and inserted in the inquiry form and data were analyzed by SPSS software. Results: In this study, 52 patients (94.2% female) were studied. 5 (9.6%) of women were pregnant.  The majority of them (69.2%) were between 15-25 years of age. Nausea and vomiting (50%) are two of the most common side effects. 5 patients (9.6%) received deferoxamine. All Patients who received deferoxamine, symptoms had less than 6 hours of onset. Most patients were hospitalized between 6-24 hours. 25% of patients took vitamins simultaneously with iron. The Serum level of iron in 3 patients (5.8%) was above 300 µg/dL. Based on this research, mortality was reported in one patient. Conclusion: In this study, the prevalence of iron poisoning was examined based on demographic and clinical characteristics. Considering the most prevalent iron poisoning in the young age group (96.2% suicides), more research in the psychological and social problems is critical for preventative behaviors.